Removal mechanism of surface cleaning on TA15 titanium alloy using nanosecond pulsed laser. (July 2021) - Li, Zhichao; Zhang, Donghe; Su, Xuan; Yang, Shirui; Xu, Jie; Ma, Rui; Shan, Debin; Guo, Bin
Highlights: Nanosecond pulsed laser is suitable for surface cleaning of oxide foil of titanium alloy. The surface color of titanium alloy is changed with increasing of laser fluence after laser cleaning. Laser thermal ablation was the main removal mechanism of oxide film on TA15 titanium alloy. The surface morphology evolution was introduced for laser cleaning of titanium alloy. Abstract: Nanosecond laser cleaning provides an alternative cleaning method that displays a significantly improved cleaning efficiency without environmental pollution. This paper reports the results of an investigation into the nanosecond pulsed laser cleaning of TA15 titanium alloy oxide film using the laser fluence and the laser head moving speed as variables. The TA15 titanium alloy oxide film changed from original silver gray to silvery white with the increase of laser fluence. However, the material surface transformed from silvery-white into yellowish-brown when the laser energy fluence exceeded 5.97 J/cm 2 . This phenomenon was attributed to the formation of titanium alloy oxides (Ti6 O, TiO2 -anatase, γ-TiO2, and TiO) after removing the oxide film using a high laser fluence at atmospheric conditions. The best surface properties were obtained when the laser fluence and the laser head moving speed were set to 3.98 J/cm 2 and 5 mm/s, respectively. The oxidation content and roughness were 2.08 wt% and 37 μm, respectively. The removal effect of the oxide film was best when the surface temperature was slightly higher than the boiling point of the oxide film, as shown by numerical calculations and analysis. The main mechanism of laser cleaning was laser ablation.